ed-Devletü'l-Osmâniyye devletün İslâmiyye müfterâ aleyhâ - 880-01 eş-Şinnâvî, Abdülazîz Muhammed. (Kahire Kahire Kahire)
4 cilt (1. c. 688, [4] sayfa ; 2. c. s. [689]-1148, [4] sayfa ; 3. c. s. [1153]-1712, [4] sayfa ; 4. c. s. [1713]-2355, [5] sayfa]